The Learning of Business Principles Meaning Model Improve as an Effort to Enhance Active Interaction and Critical Thinking - Agung Wirnarno; Ayu Mauliana Agustin (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2018)
The purpose of this study is to provide business principles learning module which bases an improvement to enhance the students of Marketing Vocational High School. It was started by need analysis and ended by testing for the user. The findings of research showed that the module guides students to think critically in finding new concepts about learning materials. An active interaction among student and feedback, upgrading, and enrichment activity where students have a full role in learning activity also happened during lesson. Besides having expediency to be applied, the module creates meaningful learning for students.